2010
DOI: 10.1075/ni.20.2.02man
|View full text |Cite
|
Sign up to set email alerts
|

Narrating traumas and transgressions

Abstract: Experiencing personal growth via reflection on negative events is well established. Yet, we know less about how people process and grow (or not) from different types of negative events, and how such narrative processing might differentially predict important outcomes, in this case, wisdom and well-being. Eighty-five community members participated in an online study examining the narrative processing and self-perceptions of traumas and transgressions, and how narrative processing predicted wisdom and well-being… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
52
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 75 publications
(55 citation statements)
references
References 27 publications
3
52
0
Order By: Relevance
“…Researchers who take a narrative perspective on personality and positive functioning have shown that people who narrate growth from challenging events tend to score high on a variety of forms of positive functioning such as egodevelopment, psychological well-being, and wisdom (e.g. Bauer & McAdams, 2004a;Pals, 2006a;Pals & McAdams, 2004;Mansfield, McLean, & Lilgendahl, 2010). However, very little work has examined whether narrating growth from a specific type of event may be associated with gains in some domains of positive functioning as opposed to others (for preliminary work in this direction see Mansfield, et al, 2010;Lilgendahl, McLean, & Mansfield, 2013).…”
Section: Is Narrating Growth In Stories Of Personal Transgressions Asmentioning
confidence: 99%
“…Researchers who take a narrative perspective on personality and positive functioning have shown that people who narrate growth from challenging events tend to score high on a variety of forms of positive functioning such as egodevelopment, psychological well-being, and wisdom (e.g. Bauer & McAdams, 2004a;Pals, 2006a;Pals & McAdams, 2004;Mansfield, McLean, & Lilgendahl, 2010). However, very little work has examined whether narrating growth from a specific type of event may be associated with gains in some domains of positive functioning as opposed to others (for preliminary work in this direction see Mansfield, et al, 2010;Lilgendahl, McLean, & Mansfield, 2013).…”
Section: Is Narrating Growth In Stories Of Personal Transgressions Asmentioning
confidence: 99%
“…It is possible that autobiographical reasoning is more hazardous for individuals from socially disadvantaged or racially ostracized groups because they experience more negative and less controllable events. As with adults, the valence of the reasoning and the nature and controllability of the event are also important determinants in the link between autobiographical reasoning and well-being for adolescents [e.g., Lilgendahl & McAdams, 2011;Mansfield, McLean, & Lilgendahl, 2010].…”
Section: Autobiographical Reasoning and Well-being Across Adolescencementioning
confidence: 99%
“…The narrative approach is chosen in research when the purpose is to understand a person's or group's identity development and construction (see, e.g., Heikkinen, 2001;Kotze, Coetzee, Elliker, & Eberle, 2015;Tasker & Delvoye, 2015) or to highlight viewpoints on coping, recovery, hope, or success (see, e.g., Bishop & Willis, 2014;Mansfield, Mclean, & Lilgendahl, 2010;Savukoski, Määttä, & Uusiautti, 2012;Uusiautti, 2008). In addition, narrative research can focus on negative life changes or experiences of some special or minority group (see, e.g., Hershberg & Lykes, 2013;Hiller, Linstroth, & Vela 2009;Hänninen, 1999;Prins, 2008).…”
Section: Discussionmentioning
confidence: 99%